A Multidisciplinary Initiative to Increase Inpatient Discharges Before Noon. (December 2016) - Kane, Marlena; Weinacker, Ann; Arthofer, Rudolph; Seay-Morrison, Timothy; Elfman, Wesley; Ramirez, Mark; Ahuja, Neera; Pickham, David; Hereford, James; Welton, Mark
Abstract : OBJECTIVE: The aim of this study is to evaluate the effect of 2 hospital-wide interventions on achieving a discharge-before-noon rate of 40%. BACKGROUND: A multidisciplinary team led by administrative and physician leadership developed a plan to diminish capacity constraints by minimizing late afternoon hospital discharges using 2 patient flow management techniques. METHODS: The study was a preintervention/postintervention retrospective analysis observing all inpatients discharged across 19 inpatient units in a 484-bed, academic teaching hospital measuring calendar month discharge-before-noon percentage, patient satisfaction, and readmission rates. Patient satisfaction and readmission rates were used as baseline metrics. RESULTS: The discharge-before-noon percentage increased from 14% in the 11-month preintervention period to an average of 24% over the 11-month postintervention period, whereas patient satisfaction scores and readmission rates remained stable. CONCLUSIONS: Implementation of the 2 interventions successfully increased the percentage of discharges before noon yet did not achieve the goal of 40%. Patient satisfaction and readmission rates were not negatively impacted by the program.